2012
DOI: 10.1016/j.geotexmem.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and chemical evolution of GCLs during filter press and oedopermeametric tests performed with real leachate

Abstract: The solid-waste decomposition inside a municipal solid-waste (MSW) landfill may be enhanced by liquid addition in order to reach landfill stabilization in a reduced period of time as compared to dry-tomb landfills. This liquid addition provides an increased leachate volume and its specific chemical composition leads to fear a degradation of the hydraulic properties of the bottom liner system, especially the mineral part. In this study, the impact of four fluids on the chemical and hydraulic properties of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The common method adopted is the "compatibility test", in which the sample is permeated with a leachate similar to that anticipated. Factors influencing the hydraulic conductivity of GCLs have been studied through extensive compatibility tests [25,53,55,[59][60][61][62][63][64][65]. Generally, the hydraulic conductivity can be affected by both internal and external causes.…”
Section: Hydraulic Conductivity and Chemical Compatibilitymentioning
confidence: 99%
“…The common method adopted is the "compatibility test", in which the sample is permeated with a leachate similar to that anticipated. Factors influencing the hydraulic conductivity of GCLs have been studied through extensive compatibility tests [25,53,55,[59][60][61][62][63][64][65]. Generally, the hydraulic conductivity can be affected by both internal and external causes.…”
Section: Hydraulic Conductivity and Chemical Compatibilitymentioning
confidence: 99%
“…To evaluate the consistency of these membranes, it is important to examine their chemical compatibility with the different fluids or the leachate to which they are subjected [22]. Based on the fine particle size, the homogeneous micropores and the high surface charges, the low hydraulic conductivity, the high adsorption capacity, and the low cost compared with geosynthetic clay (GC), natural bentonites are most prized in this context [23][24][25][26][27][28][29]. Indeed, [30] studied the shear strength of compacted clays as affected by the mineral content and wet-dry cycles and demonstrated that the cohesion and frictional strength properties were determined and linked to the proportion of clay minerals and the number of wetting and drying cycles.…”
Section: Introductionmentioning
confidence: 99%
“…However, compacted clays present problems with cracking and/ or desiccation, especially those containing an appreciable amount of bentonite [34][35][36]. Numerous studies have shown that compacted clays undergo large physicochemical properties modifications when exposed to a cycle of swelling and/or desiccation-wetting, which constitutes a surrounding variable environmental constraint [28][29][30][31][32][33][34][35][36][37][38][39]. Montmorillonite fraction, which is a dioctahedral species of the smectite mineral group, can constitute up to 95% of bentonite.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous literatures which investigated the effect of types of liquid on hydraulic conductivity of GCL or bentonite 4,[6][7][8][9][10][11][12] , but the effect of types of liquid on self-healing capacity of GCL is not well investigated. Further, there are two types of GCLs used in engineering practice, namely geomembrane supported GCL (GM-GCL) and geotextile encased GCL (GT-GCL).…”
Section: Introductionmentioning
confidence: 99%